Analisis Butir Soal Ujian Akhir Semester Ganjil Biologi Kelas XI MAN 2 Kota Jambi - Ahmad Subari; Lufri Lufri; Syamsurizal Syamsurizal (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to determine the quality of the final exam questions for the odd semester biology class XI MAN 2 Jambi City. The research subjects were 167 students of class XI MAN 2 Jambi City in the 2020/2021 academic year. This research is a descriptive study with data collection techniques through test instruments in the form of multiple choice questions, answer sheets, and answer keys. The data analysis technique used the Anates version 4.0.9 program to determine the reliability, level of difficulty, discriminatory power, distractor quality, and recap of item analysis. The results in this study indicate that the reliability value of the test items is 0.06 with very low criteria. For the item difficulty level, there are 4 questions of "very easy" difficulty, 2 questions "easy", 7 questions "medium", 4 difficult "difficult" questions, and 8 questions "very difficult". On the discriminatory power of items, there are 7 items classified into the "very bad" category, 8 items classified as "bad", 6 items classified as "enough", and 4 items classified as "good". While the results of the analysis of the quality of the item distractors, which have a distractor level of less than 51% which are generally found in each item. In addition, there are very few distractors in the percentage categories (51-75 or 126-150) and 76-125. Therefore, it can be concluded that, overall there are no questions that can be directly used, but some questions must be improved, and the rest cannot be used. There are 11 questions that need to be improved, and the remaining 14 questions that cannot be used.